Interleukin 23 Levels Are Increased in Carotid Atherosclerosis: Possible Role for the Interleukin 23/Interleukin 17 Axis. Issue 3 (March 2015) - Abbas, Azhar; Gregersen, Ida; Holm, Sverre; Daissormont, Isabelle; Bjerkeli, Vigdis; Krohg-Sørensen, Kirsten; Skagen, Karolina R.; Dahl, Tuva B.; Russell, David; Almås, Trine; Bundgaard, Dorte; Alteheld, Lars Holger; et al.
Abstract : Background and Purpose—: Interleukin (IL)-23 is a cytokine in the IL-12 family, mainly produced by antigen-presenting cells with a central role in inflammation. We hypothesize that IL-23 is also important in atherogenesis and investigate this in a population with carotid atherosclerosis. Methods—: Plasma levels of IL-23 were measured in patients with carotid artery stenosis and in healthy controls. The mRNA levels of IL-23 and its receptor, IL-23R, were measured in atherosclerotic plaques, nonatherosclerotic vessels, peripheral blood mononuclear cells, and plasmacytoid dendritic cells. Results—: Our findings were as follows: (1) patients with carotid atherosclerosis (n=177) had significantly raised plasma levels of IL-23 when compared with healthy controls (n=24) with particularly high levels in those with the most recent symptoms. (2) mRNA levels of IL-23 and IL-23R were markedly increased in carotid plaques (n=68) when compared with nonatherosclerotic vessels (n=8–10). Immunostaining showed colocalization to plaque macrophages. (3) Patients with carotid atherosclerosis had increased mRNA levels of both IL-23 and IL-23R in plasmacytoid dendritic cells, but not in peripheral blood mononuclear cells. (4) IL-23 increased IL-17 release in monocytes and particularly in peripheral blood mononuclear cells from patients with carotid atherosclerosis, but not in cells from healthy controls. (5) IL-23 gave a prominent tumor necrosis factor release in monocytes from patients with carotid atherosclerosis but not in cells from healthy controls. (6) High plasma levels of IL-23 were associated with increased mortality during follow-up. Conclusions—: We have shown an association between IL-23 and disease progression in patients with carotid atherosclerosis, potentially involving IL-17-related mechanisms. Abstract : Supplemental Digital Content is available in the text.